Strategic Formulation and Communication of Corporate Environmental Policy Statements: UK Firms’ Perspective - Kuk, George (Journal of business ethics, 2005)
This paper suggests that most of the FTSE-listed firms in the United Kingdom use corporate environmental policy statements (CEPS) to communicate their strategic intent of what environmental and social targets to attain, and broad guidelines of how they will progressively achieve all the required changes and new developments. In this paper, we link the contents of CEPS of a sample of FTSE-listed firms (from the chemical, pharmaceutical and food industry that are committed to develop business excellence) to the voluntary participation in the environmental benchmarking exercise and the various levels of environmental performance therein. The findings suggest that in contrast to their non-participating counterparts, the strategic focus of the participating firms transcends from simply mitigating any potential damages that their operations might have on the environment to business process reengineering and building new implementation capabilities. However, not all of the participating firms achieved excellence in their environmental performance, the high performing firms outweighed their counterparts on their emphasis on technological competence and competitiveness, and interestingly, the average-performing firms would use the strategic emphasis on social responsibility to compensate for their mediocre technological competence.